2019
DOI: 10.1152/ajpregu.00080.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase inhibition does not impact the pressor response during static or dynamic mechanoreflex activation in healthy decerebrate rats

Abstract: Passive limb movement and limb muscle stretch in humans and animals are common experimental strategies used to investigate activation of the muscle mechanoreflex independent of contraction-induced metabolite production. Cyclooxygenase (COX) metabolites, however, are produced by skeletal muscle stretch in vitro and have been found to impact various models of mechanoreflex activation. Whether COX metabolites influence the decerebrate rat triceps surae muscle stretch mechanoreflex model remains unknown. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
4
7
0
Order By: Relevance
“…Effect of Indo on the mechanoreflex. Consistent with our recent findings (45), in freely perfused rats (n ϭ 6), the injection of Indo into the arterial supply of the hindlimb had no effect on the pressor or cardioaccelerator response during dynamic stretch (Fig. 1, A-D).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Effect of Indo on the mechanoreflex. Consistent with our recent findings (45), in freely perfused rats (n ϭ 6), the injection of Indo into the arterial supply of the hindlimb had no effect on the pressor or cardioaccelerator response during dynamic stretch (Fig. 1, A-D).…”
Section: Resultssupporting
confidence: 92%
“…In a subset of 10 of the 14 rats used in these microdialysis experiments, we subsequently measured microdialysate PGE 2 concentration during stretch of the freely perfused and ligated hindlimb. The 1-Hz dynamic stretch protocols of the freely perfused and ligated hindlimb were performed for 4 min [which was re-quired to collect enough fluid to measure PGE 2 concentration in duplicate (45)], in random order, and with at least 10 min of recovery in between each stretch maneuver. We did not perform the stretch protocols in the four rats in which a superficial epigastric artery catheter and iliac artery and vein snare were previously placed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding in sham rats that the injection of the EP4-R or the TxA 2 -R antagonist into the arterial supply of the hindlimb had no effect on the pressor, RSNA or cardioaccelerator response to static stretch is consistent with multiple investigations which have shown that COX metabolites are not required to produce reflex cardiovascular responses in healthy subjects (Butenas et al, 2019;Drew, Blaha, Herr, Cui, & Sinoway, 2017;Morales et al, 2012;Muller et al, 2015;Rollins et al, 2019). More specifically, the present lack of effect of the EP4-R antagonist in SHAM rats is consistent with the recent of findings of Yamauchi et al (2013) using the same mode of mechanoreflex activation, and our laboratory using a dynamic mode of mechanoreflex activation (Rollins et al, 2020) in healthy control rats.…”
Section: Discussionsupporting
confidence: 90%
“…HR was measured by electrocardiogram (ADInstruments, Colorado Springs, CO, USA). The left superficial epigastric artery was cannulated with a PE‐8 catheter whose tip was placed near the junction of the superficial epigastric and femoral arteries and a reversible snare (2‐0 silk suture) was placed around the left iliac artery and vein as previously described (Rollins et al., 2019). The left calcaneal bone was severed and linked by string to a force transducer (Grass FT03; West Warwick, RI, USA), which, in turn, was attached to a rack and pinion.…”
Section: Methodsmentioning
confidence: 99%